Raising female employment : reflexions and policy tools - Pietro Garibaldi; Etienne Wasmer (Institute for the Study of Labor (IZA), 2003)
While there is consensus on the need to raise the time spent in the market by European women, it is not clear how these goals should be achieved. Tax wedges, assistance in the job search process, and part-time jobs are policy instruments that are widely debated in policy circles. The paper presents a simple model of labour supply with market frictions and heterogenous home production where the effects of these policies can be coherently analysed. We show that subsidies to labour market entry increase women's entrance in the labour market, but they also increase exits from the labour market, with ambiguous effect on employment. Subsidies to part-time do increase employment, but they have ambiguous effects on hours and market production. Finally, reductions in taxes on market activities that are highly substitutable with home production have unambiguous positive effects on market employment and production.
Keywords: J2; J0; 330; employment rate; market frictions; labour market policy; Frauenerwerbstätigkeit; Arbeitsangebot; Arbeitsmarktpolitik; Heimarbeit; Teilzeitarbeit; Wirtschaftspolitische Wirkungsanalyse; Theorie